Market Reaction to COVID-19 and Policy Response Across Different Sectors: An Event Study on ASEAN Stock Market - D. Lesmana; R. Yudaruddin (Финансы: теория и практика, 2024)
The purpose of the study is to investigate the market reaction to COVID-19 and the policy response in the ASEAN stock market. The subjects of this study are companies located in ASEAN countries (Indonesia, Malaysia, Thailand, the Philippines, and Vietnam) as many as 2349 companies. The basic methodology of this research uses the event study method using CAR (Cumulative Abnormal Return) as a measure of market reaction. We also regressed the effect of firm characteristics (SIZE, ROA, LEV, CASH, AGE) on market reaction. According to the paper’s results, the ASEAN stock market reacted negatively to the announcement of COVID-19 cases and deaths. In this condition, the markets in Malaysia, the Philippines, and Vietnam had the worst reactions to the pandemic outbreak. Moreover, the market negatively reacted to the policy response emphasizing the spread of this disease. We also find that several sectors also provided a negative reaction to COVID-19 and the policy response in the ASEAN stock market. In addition, the company’s characteristics significantly influenced the encouragement of market reactions to the pandemic and regulations. Practical implications were provided for policymakers regarding the need to consider market conditions in interventions in the spread of the health crisis. Investors should also consider the characteristics involved in handling the COVID-19 pandemic.